France : Staff Report for the 2003 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2003)
Over the past several years, implementation of IMF recommendations has been lacking not so much in intention as in pace and timing owing to political economy considerations and a strong social preference for publicly provided services. The discussions focused on how to foster a durable economic recovery while tackling long-standing threats to fiscal sustainability. The authorities were attentive to the possible adverse short-term effects of underlying fiscal adjustment on growth. The authorities acknowledged that containing health care spending growth would be a key challenge.